Pengelolaan dan Pengawasan Dana Bantuan Operasional Sekolah (BOS) Reguler Pada SD Kristen Hosana Kupang - Lassi, Novita Konnianty; Sonbay, Yolinda Yanti; Perseveranda, M.E (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze the management and supervision of Regular BOS funds at Hosana Christian Elementary School Kupang, and to analyze the obstacles in the management and supervision of Regular BOS funds at Hosana Christian Elementary School. This research uses a qualitative approach. The results of the study show that the planning and budgeting of BOS funds at SD Kristen Hosana is carried out by the BOS management team which has been carried out based on the stages of planning and budgeting in the 2022 technical year, but the preparation of the RKAS document is carried out based on the needs of the school and has not been based on the School Self-Evaluation (EDS). The implementation of BOS fund administration at Hosana Christian Elementary School is in accordance with the stages of implementing BOS fund administration in the 2022 BOS fund management technique, but the school has not made PBJ documents and conducted an inventory of goods financed from BOS funds. Reporting and accountability of BOS funds at Hosana Christian Elementary School are carried out in accordance with the stages of reporting and accountability of BOS funds in the 2022 BOS fund management guidelines. Internal supervision of Regular BOS funds at Hosana Christian Elementary School is carried out by the principal, teacher council and committee. However, the supervision carried out has not gone well.